Categorical difference as affective assemblage: experiences of Vietnamese women in the neoliberal university. Issue 5 (29th July 2022) - Pham, Xuan; Bright, David; Leahy, Deana; Welch, Rosie
ABSTRACT: In this article, we draw on interview data with three Vietnamese women to explore how categorical difference works through the ways that these women constitute themselves and are constituted as academics and doctoral students in Australian universities. Our analysis focuses on the arrangement of things that make neoliberalism an inexhaustive force, working via affective connections with other social, historical and material conditions in producing differences. Drawing on the Deleuzian concept of assemblage and contemporary feminist views of affect, we map moments when things come together via their affective capacities to produce identity categories, structures, binaries and power relations in Australian neoliberal universities. Our theorisation of categorical difference as affective assemblage is helpful in understanding the production of differences as affective arrangements of matter and meaning that are linked not only to contemporary neoliberal practices and regimes but also to historical pasts that are often Eurocentric, racialised and conventionally gendered. Given that the categorical difference is affective and contingent, we suggest that it can be surmounted when any of us, at any moment, can affect others via our capacities to think outside ordered systems no matter how powerful they might be in the thoughts of those engaged.